BLANCO RODRÍGUEZ, Juan Andrés (ed.): El asociacionismo en la emigración española a América. Zamora: UNED Zamora/ Junta de Castilla y León, 2008. - Rodríguez Teijeiro, Domingo (Studia Historica. Historia Contemporánea, 2011)
Reseña